PP24 Design of a Pickering emulsion containing an extract of the brown seaweed Dictyopteris justii with potential depigmenting activity - Hernández Muñoz, Andrea Catalina; Aragón Novoa, Diana Marcela (Revista Productos Naturales, 2025)
Marine algae are a promising source of natural cosmetic ingredients. The extraction of Dictyopteris justii was optimized using ultrasound-assisted extraction, achieving a total phlorotannin content of 2.874 ± 0.069 mg PGE/g of dry extract. The extract showed tyrosinase inhibition (IC50 = 0.51 mg/mL), suggesting its depigmenting potential. For its delivery, a Pickering emulsion stabilized with chitosan particles was formulated, reducing the use of surfactants and meeting the demand for natural and minimal-ingredient cosmetics. This study highlights the potential of D. justii, a seaweed of the Caribbean region of Colombia, as a promising source of cosmetic ingredients.